Determination of pyronaridine in whole blood by automated solid phase extraction and high-performance liquid chromatography. - Blessborn, D; Lindegårdh, N; Ericsson, O; Hellgren, U; Bergqvist, Y (2003)
A new extraction procedure for the analysis of pyronaridine in whole blood is presented. A weak cation exchanger with a carboxylic acid (CBA) sorbent was found to be a suitable solid phase sorbent for the extraction of pyronaridine. High-performance liquid chromatography with UV detection at 278 nm and an electrochemical detector at +0.75 V is used. The electrochemical detector gives higher selectivity than the UV detector. The separation was performed using a C18 reversed phase column with mobile phase of acetonitrile-phosphate buffer (0.01 mol/L, pH 2.5)- sodium perchlorate (1.0 mol/L; 22:77:1, v/v/v). The within-day RSDs were below 5% at all concentration levels between 75 nmol/L and 1500 nmol/L, and the between-day RSDs were below 14% at all concentration levels. The limit of quantification was about 50 nmol/L in 1000 microL whole blood with an RSD of 20% or less on a day-to-day basis. The stability of pyronaridine is increased if the pH is less than 3 in water solutions. In whole blood, the concentration decreases by about 10% for each freeze-thaw cycle performed. At room temperature (about 22 degrees C), pyronaridine concentration in whole blood decreases by about 10% within 12 to 24 hours.